Organic geochemistry of interstitial waters at DSDP Holes 64-474 and 64-479 - Michaelis, Walter; Mycke, Bernd; Vogt, Joern; Schuetze, Gudrun; Degens, Egon T (PANGAEA, 1982)
Studies of the nature and amount of dissolved organic matter (DOM) in pore-water solutions have been confined mostly to recent sediments (Henrichs and Farrington, 1979; Krom and Sholkovitz, 1977; Nissenbaum et al., 1972). The analyses of organic constituents in interstitial waters have not been extended to sediment depths of more than 15 meters (Starikova, 1970). Large fluctuations in organic contents of near-bottom interstitial fluids suggest that organic compounds may provide insight into the chemical and biological processes occurring in the sedimentary column. Gradients in inorganic ion concentrations have been used as indicators of diagenesis of organic matter in deep sediments and interstitial waters. Shishkina (1978) attributed the occurrence of iodine and Cl/Br ratios that deviated from the value of seawater to the breakdown of organic matter and the liberation of bromide during mineralization. Sulfate depletion and maxima in ammonia concentrations were interpreted to be a consequence of sulfate reduction reactions in pore fluids, even at depths of more than 400 meters (Miller et al., 1979; Manheim and Schug, 1978).The purpose of this chapter is to study organic carbon compounds dissolved in interstitial waters of deep sediments at Sites 474 and 479.
Supplement to: Michaelis, Walter; Mycke, Bernd; Vogt, Joern; Schuetze, Gudrun; Degens, Egon T (1982): Organic geochemistry of interstitial waters, Sites 474 and 479, Leg 64. In: Curray, JR; Moore, DG; et al. (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 64, 933-937
Keywords: Drilling/drill rig; Leg64; Glomar Challenger; Deep Sea Drilling Project (DSDP)